Job Satisfaction Job Competence, Extrinsic Motivation Towards Organizational Commitment At PT Sumber Alfaria Trijaya Malang Branch - Faizal Zahrandika; Prayekti; Eko Yulianto (Faculty of Economics, Merdeka University Surabaya, Indonesia, 2025)
This study aims to examine whether job satisfaction, job competence and extrinsic motivation affect organizational commitment at PT Sumber Alfaria Trijaya Tbk, Malang branch. This research collects samples at PT Sumber Alfaria Trijaya Tbk, Malang branch which is located in Malang city. The withdrawal method is sampling using accidental sampling using the slovin formula. Data collection was carried out through a questionnaire technique distributed via google form submitted to the human resource of PT Sumber Alfaria Trijaya Malang. The number of questionnaires processed was 68 respondents. The data was analyzed using spss. The results showed that each component has the same influence, which is positive and significant. The results showed that job satisfaction was shown to have a positive and significant effect on organizational commitment, work competence had a positive and significant effect on organizational commitment, and extrinsic motivation was shown to have a positive and significant effect on organizational commitment, and job satisfaction, work competence, and extrinsic motivation from simultaneous results (f test) were shown to have a significant positive effect together on organizational commitment at PT Sumber Alfaria Trijaya Tbk Malang branch.